If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2z + -5) = 5(z + 2) Reorder the terms: 3(-5 + 2z) = 5(z + 2) (-5 * 3 + 2z * 3) = 5(z + 2) (-15 + 6z) = 5(z + 2) Reorder the terms: -15 + 6z = 5(2 + z) -15 + 6z = (2 * 5 + z * 5) -15 + 6z = (10 + 5z) Solving -15 + 6z = 10 + 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. -15 + 6z + -5z = 10 + 5z + -5z Combine like terms: 6z + -5z = 1z -15 + 1z = 10 + 5z + -5z Combine like terms: 5z + -5z = 0 -15 + 1z = 10 + 0 -15 + 1z = 10 Add '15' to each side of the equation. -15 + 15 + 1z = 10 + 15 Combine like terms: -15 + 15 = 0 0 + 1z = 10 + 15 1z = 10 + 15 Combine like terms: 10 + 15 = 25 1z = 25 Divide each side by '1'. z = 25 Simplifying z = 25
| 1+2x=6+x | | 18(x-40)=36(x-30) | | 8x+12=77-5x | | 3(X-2)=6 | | 8(x-5)+3x=5(x+2) | | 7x-6x=19 | | 5(X-12)=-25 | | 5r+2r=0 | | 23+x=47 | | 7y+12=4y-(y+1) | | 3(X+6)=12 | | x^2y^2=2y^3-12 | | 5x-4=7x | | 4c-11=17 | | 9=1+5k-7k | | 21(x-12)=-21(x-26) | | 9x-9=6x | | 17(x-25)=-17+3(x+34) | | 7x-25=-88 | | -10-8x^2+5x^6-3x^3+x= | | (2x+14)(x-3)=90 | | 10=-3a+1 | | 3b-12=15 | | 4x^4+5x^3-7x^4= | | 6x^9+3x^9-5x^9= | | 7X+9=10X-18 | | -9+10m=161 | | 9X+25=52 | | 6X-35=77 | | (x+7)(x-3)=90 | | 2x+16=48 | | 3-4e=6 |